1998
DOI: 10.1007/s004649900750
|View full text |Cite
|
Sign up to set email alerts
|

Results of the routine use of a modified endoprosthesis to drain the common bile duct after laparoscopic choledochotomy

Abstract: The procedure proved to be technically simple, safe, and efficient, and resulted in a low morbidity rate and short hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…DePaula et al [5], especially, suggested T-tube use as a routine procedure. However, upper digestive endoscopy was required for its removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DePaula et al [5], especially, suggested T-tube use as a routine procedure. However, upper digestive endoscopy was required for its removal.…”
Section: Discussionmentioning
confidence: 99%
“…In selected patients, the bile duct can be closed primarily. Another option is antegrade insertion of a biliary stent, as proposed by DePaula [5]. We modified the original biliary stent by eliminating the proximal biliary flap while maintaining the distal duodenal flap.…”
mentioning
confidence: 99%
“…Endoprosthesis followed by primary closure of the CBD is another alternative method for managing CBD stones. Although there are reports suggesting that biliary endoprosthesis leads to lower morbidity and a shorter hospital stay than T-tube drainage [19], it has disadvantages such as the need for an upper digestive endoscopy to retrieve the stent 4 to 6 weeks after surgery. At the same time, cholangiography is impossible during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a safe and effective method, it still has a high complication rate, 16.4% as reported by Martin et al [1]. To avoid the complications associated with T-tubes, several alternative methods have been used to treat common bile duct (CBD) stones, such as primary closure of the CBD without drainage, primary closure of the CBD over endoprosthesis, and transcystic duct tube drainage [2][3][4][5]. However, these methods have their own limitations and drawbacks.…”
mentioning
confidence: 94%
“…Although we enthusiastically introduced primary closure of the common bile duct (CBD) [1][2][3][4], elimination of the T tube after LCBDE requires further investigation [5]. Biliary decompression surgery should not be ignored in consideration of the potential for temporary obstruction at the lower end of the CBD the first few days after manipulations to extract duct calculi or retained stones [6,7].…”
mentioning
confidence: 99%